2007
DOI: 10.1007/s00440-007-0117-7
|View full text |Cite
|
Sign up to set email alerts
|

How do random Fibonacci sequences grow?

Abstract: We study two kinds of random Fibonacci sequences defined by $F_1=F_2=1$ and for $n\ge 1$, $F_{n+2} = F_{n+1} \pm F_{n}$ (linear case) or $F_{n+2} = |F_{n+1} \pm F_{n}|$ (non-linear case), where each sign is independent and either + with probability $p$ or - with probability $1-p$ ($0 Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Moreover, φ λ is increasing, and since it is onto, φ λ is continuous. We observed in [5] some connection, when λ = 1, with Minkowski's question mark function. Translated in the context of the present paper, this connection can be written as follows:…”
Section: éLise Janvresse Benoît Rittaud and Thierry De La Ruementioning
confidence: 82%
See 1 more Smart Citation
“…Moreover, φ λ is increasing, and since it is onto, φ λ is continuous. We observed in [5] some connection, when λ = 1, with Minkowski's question mark function. Translated in the context of the present paper, this connection can be written as follows:…”
Section: éLise Janvresse Benoît Rittaud and Thierry De La Ruementioning
confidence: 82%
“…The motivations for the present article stem from several works by the same authors [5,6], where the exponential growth of random Fibonacci sequences with parameter λ is studied. In [6], the case λ = λ k for some integer k ≥ 3 is solved and involves a probability distribution on R + invariant under some dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…β > 0, and studied further in [14], where it was shown that there was a critical threshold β such that β > β would cause exponential growth in the sequence, while β < β would cause exponential decay. Further work was performed in [15], where the exponential growth rate of…”
Section: Random Sequences and Dynamical Systemsmentioning
confidence: 99%
“…The method involves using Stern-Brocot sequences, Furstenberg's Theorem (see Theorem 2.3) and the invariant measure to compute λ. We also point to the work of [14,13,12] where the authors generalized the results of Viswanath by letting 0 < p ≤ 1 and treating λ as a function of p which bears some similarity to the model we study in Section 3. They also considered the non-linear case.…”
mentioning
confidence: 92%